Comparison between Olive Oil and Nano-Bio Fusion Gel and their Role in the Treatment of Alveolar Osteitis: A Double-Blind Randomized Trial - Khan, Zafar Ali; Prabhu, Namdeo; Ahmed, Naseer; Issrani, Rakhi (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Alveolar osteitis is a painful condition that occurs after tooth extraction. This condition has been treated with various chemical and herbal formulations that are found to be efficacious with different success rates. Objectives: The present study is aimed to evaluate and compare the efficacy of organic olive oil and Nano-Bio Fusion (NBF) gel in the management of alveolar osteitis. Materials and Methods: 90 patients who were diagnosed with alveolar osteitis following non-surgical dental extractions were selected and randomly divided into two groups. The extraction socket was irrigated with warm normal saline followed by insertion of sterile gauze soaked in organic olive oil in Group I patients (n=45) and with NBF gel in Group II patients (n=45). The patients were recalled for the change in dressings on day 3, day 5 and day 7. The subjects were evaluated for the following parameters on 7th day; pain, gingival erythema, granulation tissue and the extraction socket margin. Data were analyzed using Friedman test and Mann-Whitney U test. P≤0.05 was considered statistically significant. Results: The mean VAS score on day 1 for group I was 8.9 and group II was 8.6. The mean VAS score for both the groups was zero on day 7 though the participants of group II reported better pain relief from day 3 to day 7 when compared with group I patients. Subjects treated with olive oil showed a mildly inflamed gingival to a normal pink variant on day 7. However, all the subjects treated with NBF gel presented with healthy pink gingival on day 7. There was significant improvement in the healing of the margin in both cases. Conclusion: Compared to the olive oil, NBF gel helps in enhanced healing in cases of alveolar osteitis.
Keywords: Alveolar osteitis; Pain; Extraction; Mandibular third molars; Olive oil; Nano-Bio Fusion